The kinetics of hydrogen peroxide reduction on rare earth doped UO2 and SIMFUEL - Zhu, Ziyan; Ly, Malin; Liu, Nazhen; Noël, James J.; Shoesmith, David W. (Frontiers in Materials, 2022)
The electrochemical reduction of hydrogen peroxide has been studied in sodium chloride solutions containing various anions (bicarbonate/carbonate, sulphate) on Gd-UO2, Dy-UO2 and a SIMFUEL (UO2 doped to simulate spent nuclear fuel). The reaction was observed to proceed via the chemical oxidation of the surface to produce UV followed by its subsequent electrochemical reduction. The reaction was faster on the SIMFUEL surface due to the availability of the oxygen vacancies required to incorporate the OII ions necessary to maintain charge balance. Bicarbonate/carbonate, but not sulphate, was found to suppress peroxide reduction. This could be caused either by peroxide decomposition in solution or by the catalysis of peroxide reformation via the reaction of surface hydroxyl radicals with bicarbonate/carbonate to form carbonate radicals which subsequently decompose by reaction with water. The noble metal particles present in the SIMFUEL appear to play only a minor role in the reduction process.